THE NORTH KOREAN CARD IN US-CHINA RELATIONS: HOW SHOULD IT BE PLAYED?. Issue 3 (27th May 2021) - Farago, Niv; Merrill, John
Abstract: For two decades, successive US administrations have overplayed the importance of pressure tactics and Chinese support for denuclearizing North Korea. However, the continued development of North Korea's nuclear and missile programs reflects not only gridlock in US-North Korea relations, but also Pyongyang's growing suspicions over China's commitment to the Kim regime. By supporting and enforcing tougher sanctions, Beijing has only reinforced North Korean distrust and concern. At the same time, realizing that excessive pressure on a nuclear North Korea might result in a cataclysmic regional crisis, China has been careful not to push the Kim regime into a corner. Apparently, China is not as valuable an asset to the United States on North Korea, as some believe. Instead, the Biden administration should engage the Kim regime, focus on trust building, and aim for a step-by-step nuclear deal in which freezing and gradual disarmament are commensurate with sanctions relief and eventual normalization.